2006
DOI: 10.1088/0953-8984/18/31/038
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of local electronic and magnetic properties in pure and electron-doped Nd2CuO4

Abstract: The local electronic structure of Nd2CuO4 is determined from ab-initio cluster calculations in the framework of density functional theory. Spin-polarized calculations with different multiplicities enable a detailed study of the charge and spin density distributions, using clusters that comprise up to 13 copper atoms in the CuO2 plane. Electron doping is simulated by two different approaches and the resulting changes in the local charge distribution are studied in detail and compared to the corresponding change… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…4,5 It is found that doping with electrons predominantly decreases n d but only slightly n p . In other words, the doped electrons in Ln A comparative interpretation of the NQR results from hole-doped and electron-doped cuprates is complicated by several factors: [9][10][11] (i) the EFG at a copper or oxygen nucleus from a hole in its own electron shell (here called "self EFG"); (ii) the EFG from differently charged nearest neighbors in the CuO 2 plane (abreviated "nn EFG"); (iii) the presence or absence of O 2− ions above and beneath Cu 2+ ions-called "apical" oxygen ions-and of O 2− above and beneath O 2− ions in the CuO 2 plane according to the T or T structure; (iv) hybridization of Cu 3d x 2 −y 2 and O 2p σ orbitals leading to covalent bond, (v) deformation of electron shells in the crystal, and (vi) higher-order effects.…”
Section: Commonalities In the Stripe And Nqr Studies Of La 2−x Sr X Cuomentioning
confidence: 99%
“…4,5 It is found that doping with electrons predominantly decreases n d but only slightly n p . In other words, the doped electrons in Ln A comparative interpretation of the NQR results from hole-doped and electron-doped cuprates is complicated by several factors: [9][10][11] (i) the EFG at a copper or oxygen nucleus from a hole in its own electron shell (here called "self EFG"); (ii) the EFG from differently charged nearest neighbors in the CuO 2 plane (abreviated "nn EFG"); (iii) the presence or absence of O 2− ions above and beneath Cu 2+ ions-called "apical" oxygen ions-and of O 2− above and beneath O 2− ions in the CuO 2 plane according to the T or T structure; (iv) hybridization of Cu 3d x 2 −y 2 and O 2p σ orbitals leading to covalent bond, (v) deformation of electron shells in the crystal, and (vi) higher-order effects.…”
Section: Commonalities In the Stripe And Nqr Studies Of La 2−x Sr X Cuomentioning
confidence: 99%
“…Previously, we have investigated in Refs. [19,20] the changes of the copper EFG values that occur upon doping in La 2 CuO 4 and in Nd 2 CuO 4 . We found that it is sufficient to concentrate on those MOs which contain partially occupied 3d x 2 −y 2 and 3d 3z 2 −r 2 AOs at the target nucleus.…”
Section: Modelmentioning
confidence: 99%
“…A very important feature of this code is that its accuracy and cost can be tuned in a wide range, from quick exploratory calculations to high quality simulations matching the accuracy of plane-wave methods. approximation (GGA) [22][23][24]. It adopts norm-conserving pseudopotentials using Troullier and Martins scheme in fully nonlocal form and valence electrons described in a basis set, a linear combination of numerical atomic orbital (LCAO).…”
Section: Introductionmentioning
confidence: 99%